STUDY OF LITERATURE ON VARIATION IN THE APPLICATION OF THE THINK PAIR SHARE TYPE OF COOPERATIVE LEARNING MODEL AND ITS EFFECT ON STUDENTS’ LEARNING COMPETENCIES - Fadika Hayyuni; Relsas Yogica; Zulyusri Zulyusri; Yusni Atifah (ATRIUM PENDIDIKAN BIOLOGI, 2021)
The purpose of this study was to analyze the effect of the application of the Think Pair Share learning model on the learning competence students based on literature studies. The type of research used is descriptive research with literature studies. The data used is in the form of secondary data, namely in the form of articles in the journal that has been accredited by SINTA totaling 5 articles and related to the application of the Think Pair Share type cooperative learning model to the leraning competence students. The research sample is all members of the sample who are applied with the Think Pair Share type cooperative learning model found in predetermined articles.